Bewusstsein, Antinomien und System. Hölderlins Auseinandersetzung mit Fichtes Philosophie in den Briefen (1794-1796) (Studia theodisca, 2017)
Through the analysis of the letters about Fichte’s philosophy, with particular regard to the letter to Hegel (January 26th 1795), the present contribution discusses Hölderlin’s understanding of the philosophical issues which are included in the concepts “consciousness”, “antinomies” and “system”.